Store Atmosphere on Consumer Satisfaction at Supermarket Surya Indah In Bone District - Widya Sari, Andi Indah; Yamin, Muh Nur; Baharuddin, Aris (Universitas Negeri Makassar, 2023)
This study aims to determine the store atmosphere on consumer satisfaction at Surya Indah Swalayan in Bone Regency. This study uses a quantitative approach to the type of descriptive research with a population of 7,512 consumers and the sample in this study as many as 93 consumers. Data collection techniques used through observation, questionnaires (questionnaire), and documentation. The data that has been obtained from the research results are processed using data analysis and using the SPSS.20 software application which consists of descriptive analysis techniques and inferential statistical analysis. The results of the research obtained indicate that the indicators for each of the variables used, where the store atmosphere variable shows that the indicators used in this study are in the good category. As for the indicators on the variable consumer satisfaction shows in the very good category. Based on the results of inferential analysis, Pearson's correlation is 0.420, which means that there is a moderate/sufficient relationship between the two variables. So it can be concluded that there is a significant influence between store atmosphere on consumer satisfaction at Surya Indah Swalayan in Bone Regency.